Comparative effectiveness of transitional care services in patients discharged from the hospital with heart failure: a systematic review and network meta‐analysis. (24th February 2017) - Van Spall, Harriette G.C.; Rahman, Tahseen; Mytton, Oliver; Ramasundarahettige, Chinthanie; Ibrahim, Quazi; Kabali, Conrad; Coppens, Michiel; Brian Haynes, R.; Connolly, Stuart
Abstract: Aims: To compare the effectiveness of transitional care services in decreasing all‐cause death and all‐cause readmissions following hospitalization for heart failure (HF). Methods and results: We searched PubMed, Embase, CINAHL, and Cochrane Clinical Trials Register for randomized controlled trials (RCTs) published in 2000–2015 that tested the efficacy of transitional care services in patients hospitalized for HF, provided ≥1 month of follow‐up, and reported all‐cause mortality or all‐cause readmissions. Our network meta‐analysis included 53 RCTs (12 356 patients). Among services that significantly decreased all‐cause mortality compared with usual care, nurse home visits were most effective [ranking P ‐score 0.6794; relative risk (RR) 0.78, 95% confidence intervals (CI) 0.62–0.98], followed by disease management clinics (DMCs) (ranking P ‐score 0.6368; RR 0.80, 95% CI 0.67–0.97). Among services that significantly decreased all‐cause readmission, nurse home visits were most effective [ranking P ‐score 0.8365; incident rate ratio (IRR) 0.65, 95% CI 0.49–0.86], followed by nurse case management (NCM) (ranking P ‐score 0.6168; IRR 0.77, 95% CI 0.63–0.95), and DMCs (ranking P ‐score 0.5691; IRR 0.80, 95% CI 0.66–0.97). There was no significant difference in the comparative effectiveness of services that improved each outcome. Nurse home visits had the greatest pooled cost‐savings (3810 USD, 95% CI 3682–3937), followed by NCM (3435 USD, 95% CI 3224–3645), and DMCs (245 USD, 95% CI −70 to 559). Telephone, telemonitoring, pharmacist, and education interventions did not significantly improve clinical outcomes. Conclusion: Nurse home visits and DMCs decrease all‐cause mortality after hospitalization for HF. Along with NCM, they also reduce all‐cause readmissions, with no significant difference in comparative effectiveness. These services reduce healthcare system costs to varying degrees.